High-power pre-chirp managed amplification of femtosecond pulses at high repetition rates. (4th June 2015) - Liu, Yang; Li, Wenxue; Zhao, Jian; Bai, Dongbi; Luo, Daping; Zeng, Heping
Abstract: Femtosecond pulses at 250 MHz repetition rate from a mode-locked fiber laser are amplified to high power in a pre-chirp managed amplifier. The experimental strategy offers a potential towards high-power ultrashort laser pulses at high repetition rates. By investigating the laser pulse evolution in the amplification processes, we show that self-similar evolution, finite gain bandwidth and mode instabilities determine pulse characteristics in different regimes. Further average power scaling is limited by the mode instabilities. Nevertheless, this laser system enables us to achieve sub-50 fs pulses with an average power of 93 W.